(untitled) (Journal of Engineering, 2015)
In this work, strains and dynamic crack growth were studied and analyzed in thin flat plate with a surface crack at the center, subjected to cycling low velocity impact loading for two types of aluminum plates (2024, 6061). Experimental and numerical methods were implemented to achieve this research. Numerical analysis using program (ANSYS11-APDL) based on finite element method used to analysis the strains with respect to time at crack tip and then find the velocity of the crack growth under cycling impact loading. In the experimental work, a rig was designed and manufactured to applying the cycling impact loading on the cracked specimens. The grid points was screened in front of the crack tip to measure the elastic-plastic displacements in the x and y direction by grid method, from which the strains are calculated. The results show that the strains increase with increasing in the crack length. It was found that the cumulative number of cycles leads to increase in the strain values with increasing in crack growth velocity.